2023
DOI: 10.1002/csc2.21118
|View full text |Cite
|
Sign up to set email alerts
|

Effect of uptake of improved seed potato and donor‐funded training on smallholder farmers’ market participation

Ednah Kangogo,
David Jakinda Otieno,
Julius Okello
et al.

Abstract: Enhancing the productivity of crops through the adoption and uptake of technologies improves farmers' socio‐economic status through increased market participation. However, smallholder farmers in Sub‐Saharan Africa (SSA) face a myriad of challenges that make it difficult for them to access and participate in the output markets. Like most SSA countries, the uptake of improved technologies is still low in Malawi. This paper examines the relationship between uptake of improved potato seed and donor‐funded trainin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 33 publications
0
1
0
Order By: Relevance
“…Results from the study undertaken by Ngozi and Feleke (2024) in Tanzania found that youth participation in a consortium business model being employed by Kilimo Trust had a positive, significant effect on youth retention in potato production, but the magnitude of higher profits per hectare compared to non-participants was small. Kangogo et al (2024) studied the uptake of improved potato seed and donorfunded training on market participation in Malawi and found positive significant results.…”
Section: Crop Sciencementioning
confidence: 99%
“…Results from the study undertaken by Ngozi and Feleke (2024) in Tanzania found that youth participation in a consortium business model being employed by Kilimo Trust had a positive, significant effect on youth retention in potato production, but the magnitude of higher profits per hectare compared to non-participants was small. Kangogo et al (2024) studied the uptake of improved potato seed and donorfunded training on market participation in Malawi and found positive significant results.…”
Section: Crop Sciencementioning
confidence: 99%